Corporate social responsability dimensions and sustainable entrepreneurship - Aldeia, Susana (2021)
The topics of entrepreneurship , corporate social responsability (CSR) and socially committed entrepreneurial strategies are commonly applied in different contexts, however, most of the times there's a lack of consonance and coherence as far as these matters are concerned. [...]